IMPROVING STUDENTS' WRITING SKILL IN NARRATIVE TEXT BY USING SHORT VIDEO AT SMK SARASWATI 3 TABANAN - NI PUTU AYU KARTIKA SARI DEWI; NI PUTU DINA SHANTI; I GUSTI BAGUS YOGA WIDIADNYA; I MADE SUAMBA; IDA AYU OKA PURNAMI (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2025)
This study aims to investigate the use of short videos to improve students’ writing skills of narrative texts at the vocational high school. This study is categorized as classroom action research. The use of short videos helps students understand the generic structures of narrative texts. During learning processes, students are asked to analyze the narrative structures from the introductory to the conclusion paragraph. (Manalu & Tarigan & Sitopu & Silaban, 2021). In the first cycle, students demonstrated moderate improvement in writing narrative texts. However, issues such as limited vocabulary and incorrect use of tenses were still apparent. After analyzing these challenges during the reflection phase, additional activities were incorporated in the second cycle, including vocabulary-building exercises and focused grammar drills. By the end of the second cycle, the students showed substantial progress. The average writing score increased from 65 in the pre-test to 75 in the post-test of the first cycle, and further to 85 in the post-test of the second cycle. Moreover, students displayed enhanced creativity and engagement, which were evident in the originality and coherence of their stories. The use of short videos provided visual context, making it easier for students to generate ideas and structure their narratives effectively.